ONLINE MEDIA REPORTING ABOUT FOREIGN COUNTRIES IN SERBIA, CROATIA AND BOSNIA AND HERZEGOVINA - Milosavljević, Ilija Ž. (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2017)
In post-global society the media space intended for world news is more limited, therefore journalists are forced daily to perform a selection of relevant events, processes and personalities based on certain criteria. These criteria are closely related to the political, cultural, ideological, economic, religious, security and other features of the community to which media belong, and this can lead to the creation of different pictures of the world in different societies. The aim of paper is to determine whether there are differences in the manner of selection and presentation of world events in the online media between geographically, linguistically and culturally close nations – Serbia, Croatia and Bosnia and Herzegovina? The main hypothesis is that there are differences in the selection of subjects, the focus of attention, context and manner of presentation of foreign news in the online media in Serbia, Croatia and Bosnia and Herzegovina. The analysis was conducted on one week sample in three online media from Serbia (novosti.rs), Croatia (24sata.hr) and Bosnia and Herzegovina (nezavisne.com), using the statistical methods and comparative content analysis. The results confirm differences in the presentation of events influenced by political-ideological and political-historical and also religious differences among the countries, but also the results show that similarities exist, due to the dominant criteria of negativity and importance of elite nations.
Keywords: Bosnia and Herzegovina; Croatia; Serbia; online media; agenda setting; news values; foreign news